Family support, social security, commercial insurance, and aging anxiety among Chinese residents: a study based on the 2021 CGSS data - Gu, He; Tan, Qingli; Guo, Yongxing; He, Han; Zhang, Yu (Frontiers in Public Health, 2025)
ObjectiveAging anxiety has emerged as a significant issue affecting the mental health of Chinese residents and social stability. This study utilizes data from the 2021 Chinese General Social Survey (CGSS) to examine aging anxiety among Chinese residents and the effects of family support, social security, and commercial insurance on this anxiety.MethodsDescriptive statistics were first used to examine aging anxiety and its overall situation. Group differences in aging anxiety were analyzed using t-tests or ANOVA. A multiple linear regression assessed the influence of family support, social security, and commercial insurance on aging anxiety, controlling for socio-demographic variables. A robustness test further evaluated the stability of these effects by increasing control variables. Finally, heterogeneity analysis explored the differential impact of independent variables across groups by region, gender, education, and health status.ResultsThe overall aging anxiety level is moderate (3.39 ± 0.96), with health, psychological, and economic anxiety scores of 3.65 ± 1.12, 3.28 ± 1.14, and 3.24 ± 1.21, respectively. Higher anxiety was reported by rural residents, women, those with lower education, income, poor health, and no pension or medical insurance. Significant differences were observed across residence, gender, and health status, but not for work status, marital status, or number of children. Multiple linear regression revealed that family income and basic pension insurance significantly influence aging anxiety, while commercial insurance had no significant effect (p < 0.05).ConclusionThis study highlights moderate aging anxiety among Chinese residents, particularly in rural areas, women, low-income individuals, and those in poor health. To address this, policy should prioritize strengthening the social security system, expanding pension coverage, enhancing basic pension benefits, and improving living standards for rural and low-income urban residents. These actions are crucial for safeguarding psychological well-being and ensuring social stability.